Kynurenine pathway metabolites in cerebrospinal fluid and blood as potential biomarkers in Huntington's disease. Issue 2 (5th May 2021) - Rodrigues, Filipe B.; Byrne, Lauren M.; Lowe, Alexander J.; Tortelli, Rosanna; Heins, Mariette; Flik, Gunnar; Johnson, Eileanoir B.; De Vita, Enrico; Scahill, Rachael I.; Giorgini, Flaviano; Wild, Edward J.
Abstract: Converging lines of evidence from several models, and post‐mortem human brain tissue studies, support the involvement of the kynurenine pathway (KP) in Huntington's disease (HD) pathogenesis. Quantifying KP metabolites in HD biofluids is desirable, both to study pathobiology and as a potential source of biomarkers to quantify pathway dysfunction and evaluate the biochemical impact of therapeutic interventions targeting its components. In a prospective single‐site controlled cohort study with standardised collection of cerebrospinal fluid (CSF), blood, phenotypic and imaging data, we used high‐performance liquid‐chromatography to measure the levels of KP metabolites—tryptophan, kynurenine, kynurenic acid, 3‐hydroxykynurenine, anthranilic acid and quinolinic acid—in CSF and plasma of 80 participants (20 healthy controls, 20 premanifest HD and 40 manifest HD). We investigated short‐term stability, intergroup differences, associations with clinical and imaging measures and derived sample‐size calculation for future studies. Overall, KP metabolites in CSF and plasma were stable over 6 weeks, displayed no significant group differences and were not associated with clinical or imaging measures. We conclude that the studied metabolites are readily and reliably quantifiable in both biofluids in controls and HD gene expansion carriers. However, we found little evidence to support a substantial derangement of the KP in HD, at least to the extent that it is reflected by the levels of the metabolites in patient‐derived biofluids. Abstract : Converging lines of evidence from non‐human models support the involvement of the kynurenine pathway in Huntington's disease. However, evidence in living humans is limited. In a prospective study with standardised collection of cerebrospinal fluid and blood, we used high‐performance liquid‐chromatography to analyse this pathway. We concluded that the selected metabolites are readily and reliably quantifiable. Yet, we found little evidence to support a substantial derangement of the kynurenine pathway in Huntington's disease, at least to the extent that it is reflected by the levels of the metabolites in patient‐derived biofluids. 3‐HK, 3‐hydroxykynurenine; KYNA, kynurenic acid; QUIN, quinolinic acid.